Tinjauan Tentang Nilai Perusahaan Berdasarkan Performa Finansial - Annisa Tri Widyastuti; Shinta Permata Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Firm value is the economic value of a company that reflects how much the company is valued by the market, investors, and other stakeholders. This study aims to examine the effect of financial performance on firm value in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The independent variables include liquidity, solvency, profitability, asset utilization, and market valuation, while the dependent variable is firm value, that measured by Price to Book Value (PBV). This study uses a quantitative approach employing purposive sampling and secondary data obtained from annual reports and audited financial statements through the official website of the Indonesia Stock Exchange and related companies. The data analysis method uses multiple linear regression analysis using the STATA 18 software. The results of the study show that liquidity, solvency, and market valuation have an effect on firm value, while profitability and asset utilization do not have an effect on firm value.